Mindanao resistance writing reinscriptions of cultural identity in Mindanao postcolonial prose fiction - Puno, Nancy Fe M. (2006)
This study examines the interface of language and literature in the post-colonial re-inscriptions of the tri-people communities of Mindanao: the Moros, the Lumads and the Christianized groups. The critical re-reading of the selected Mindanao texts reveal that there is a pattern of resistance culture in the use of linguistic and literary strategies. These literary strategies as tools of resistance writing re-inscribe the cultural communities of Mindanao, the indigenous and migrant groups whose pre-colonial and even pre-Islamic traditions and traditional forms are strongly rooted in their own indigenous belief systems. The interrogation of values and mean- ing as a literary strategy attempts to re-write the histories and pseudo-histories of the Mindanaon from their own re-memories aimed at the re-constitution of shattered cultural identities. In the appropriation of the colonizer's language, the use of linguistic strategies in text and outside of the text underscores the most salient feature of resistance writing: the abrogation and appropriation of the colonial language, English. The use of code-switching and inter-language reveals the cultural provenience of the code while the use of editorial intrusions, in and out of text, not only establishes social distance but also bridges the culture gap by validating the use of the regional variety of English as the appropriated language, functional in the Asian context. The use of untranslated words and vernacular transcriptions forces the reader to cross the cultural gap without the help of translation, thus making it the ultimate in resistance writing. The texts as postcolonial counter-discourse are the struggles of the people.
Keywords: Folk literature, Philippine; Literature -- Criticism and interpretation; Literature -- Translations; Mindanawon literature